Analysis of employer’s feedback on the employment of People with Disabilities (PWDs) - Omar, Muhd Khaizer; Mat Rashid, Abdullah; Saripan, M. Iqbal; Mohd Puad, Mohd Hazwan; Ismail, Irwan Mahazir (Institute of Advanced Scientific Research, 2020)
Over the years, studies related to people with disabilities (PWDs) have been performed as a result of the government’s concern on the future of this group as a part of the national grassroots. The valuable contribution of people of this group has also led to a negative perception and connotation of people, which reduces their opportunity for employment. This article presents the initial investigation of the descriptive analysis of Malaysian employers’ perception of the employment of PWDs in their organization and the validation of the replicated instrument before the actual study. A pilot study was conducted on a registered organization with the Malaysia External Trade Development Corporation (MATRADE). The profile of each organization was accessible online via MATRADE website, with the compilation of email addresses as the method of questionnaire distribution. The questionnaire was replicated from the Survey of Employer Perspectives on the Employment of People with Disabilities provided by The U.S. Department of Labor, Office of Disability Employment Policy (ODEP). The instrument was then distributed to two-hundred organizations. Out of 37 responses collected after the provision of three reminders to the organizations, 20 completed responses were gathered and used for reliability analysis. The results of this analysis are presented in this article. The pilot testing is vital to ensure that the questionnaire determines the employers’ feedback on the employment of PWDs, which may warrant the validity of the actual study for future discussion. The pilot test reveals six constructs reliability analysis, namely (a) employability skills, (b) PWDs recruitment efforts, (c) factors of PWDs employment, (d) challenges and barriers, (e) concern and perception, (f) career development for PWDs, and (g) strategies and incentives for employers in hiring PWDs.